PHARMACEUTICAL COMPULSORY LICENSING IN EMERGING MARKETS: IS IT A WELFARE LICENSING OR THREAT? - RITIKA SHARMA; SMITA SAHU (International Journal of Pharma and Bio Sciences, 2014)
India, which has 2/3rd patent protection to foreign MNC pharma companies and 24% contribution of generic industry to economy, took a big step of Compulsory Licensing of life saving drugs to Indian Generic Pharma company, Natco Pharma ,against the MNC patentee Bayor Corporation. Decision lands up as a boon for the Indian as well as global patients who depend upon Indian Generic Industry for affordable drugs. India took its first compulsory license in 2012 as till 2005, Indian Patent Act does not have the provision of Pharmaceutical and health related Product Patent. The decision also came up with the future prospective for generic companies to take the initiative in the R & D as well as drug development for their own. Also, compulsory licensing burdens the foreign patentees to commercialize the patented drug in Indian market and manufacture it in the Indian Territory, which leads to a healthy competition in pharma industry. This paper extensively studies the overview and post CL implications in the various spectrum of innovation, fair competition ,countries economy ,price control, research trend, Licensing trend of pharmaceutical sector vis a vis Foreign counterparts.